1987
DOI: 10.1111/j.1550-7408.1987.tb03142.x
|View full text |Cite
|
Sign up to set email alerts
|

Encystment in the Hypotrichous Ciliate Paraurostyla weissei: Ultrastructure and Cytochemistry1

Abstract: The cyst wall of Paraurostyla weissei consists of four morphologically distinct layers. It shows an ultrastructure and composition similar to that of the previously described kinetosome‐resorbing cysts, and its cytoplasm displays characteristics of “urostylid‐type” cysts. Therefore it is possible to consider it a “transition ciliate” between Stichotrichina and Sporadotrichina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…Works in progress of our laboratory support this idea; none of the cystic precursors appearing in the cytoplasm (granules or vacuoles), as described in hypotrichous ciliates (Oxytricha fallax [12], Pleurotricha [21], Gastrostyla steinii [32], Laurentiella acuminata [13], Oxytricha bifaria [31], Paraurostyla weissei [5]) are found during the encystment of Euplotes muscicola. In contrast, it seems that the synthesis of chitino-proteic microfibrils should take place at the plasmic membrane level, according to the process observed in arthropodial cuticles [10].…”
Section: Morphology -mentioning
confidence: 83%
“…Works in progress of our laboratory support this idea; none of the cystic precursors appearing in the cytoplasm (granules or vacuoles), as described in hypotrichous ciliates (Oxytricha fallax [12], Pleurotricha [21], Gastrostyla steinii [32], Laurentiella acuminata [13], Oxytricha bifaria [31], Paraurostyla weissei [5]) are found during the encystment of Euplotes muscicola. In contrast, it seems that the synthesis of chitino-proteic microfibrils should take place at the plasmic membrane level, according to the process observed in arthropodial cuticles [10].…”
Section: Morphology -mentioning
confidence: 83%
“…Oxytrichid ciliates show the highest number of cyst layers (Calvo et al 1983, Delgado et al 1987, Gutiérrez et al 2003. The cyst wall of R. quadrinucleata is composed Taxonomic classification of the species to the class and family *Description of surface cyst of B. truncatella by Beers (1948) and Foissner (1993).…”
Section: Resting Cysts Of a Soil Ciliate 87mentioning
confidence: 99%
“…Based on transmission electron microscopy analysis, the surface ornamentation of R. quadrinucleata belongs to "spines" and are generated by ectocyst lamellae. The ectocyst origin of surface ornamentations are typical for Paraurostyla weissei by Delgado et al (1987), Steinia sphagnicola by Foissner et al (2007), Pleurotricha sp. by Matsusaka (1976) and Oxytricha bifaria [now accepted as Stylonychia bifaria (Stokes, 1887) Berger, 1999] by Verni et al (1984).…”
Section: Resting Cysts Of a Soil Ciliate 87mentioning
confidence: 99%
“…It has been concluded that oxytrichids have four layers in their cyst wall, and that euplotids have two layers, and that urostylids have three layers (Walker et al 1975;Rios et al 1985;Delgado et al 1987). The wall of resting cysts is composed of ectocyst, mesocyst, endocyst, and granular layers in A. cf.…”
Section: The Cyst Wall and Macronucleimentioning
confidence: 99%